Pattern of Eye Diseases in Children at Secondary Level Eye Department in Karachi - Shahid Wahab, Zareen Mahdi, Shahnawaz Munami, Ziauddin Ahmed Shaikh, Haroon Awan (Pakistan Journal of Ophthalmology, 2006)
Purpose: To asses the pattern of common eye diseases in children of 0-15 years of age attending an out patient eye department, Sindh government hospital, new Karachi. Material and Methods: A modified WHO/PBL eye examination proforma in respect of each child was filled in for recording of personal history, examination results and treatment required. The pattern of eye diseases affecting the children of new Karachi causing blindness and visual impairment according to age and sex were assessed. Results: A total of 520 children of which 57.1% were male and 42.9 % female were examined and recorded squint 17.7% was the most common ocular morbidity followed by bacterial conjunctivitis 14.8%, Vernal Catarrh 12.1%, trauma 9.6%, blephritis 7.9%, vitamin A deficiency 7.5%, lid problems 7.5% (chalazion, stye), Corneal ulcers and Corneal opacity accounted for 9.4% ,nasolacrimal duct block 3.7%, trachoma 2.3%, and Cataract 1.4%. Out of 520, 334 children in age group 7-15 i.e. 64.2% were examined for refractive errors and 56.8 %found to be visually impaired. Others causes were less than 1%. Conclusion: The distribution of male and female children was similar in different age groups. The number of eye disease was highest in children age group 7-15 i.e. 64% followed by age group 1-6, i.e. 27.5%, and children less than 1 year were 8.3%.